A mark through Time: academic transcendence from university teaching practice - Morales Zárate, Carlos Mario (2021)
Contemporary education pretends to leave behind traditional teaching models, where the person in front of the student body dominated the classroom; currently, bilateral participation is favoured for the construction of knowledge. This article aims to analyse the perception that higher education teachers have of their role in teaching and how their practice influences the lives of their students; for this, a qualitative research with a phenomenological approach was carried out, in which some interviews were conducted during the second semester of 2020, with a group of teachers from a higher institution located in the Mexican state of Tabasco. It was identified that in order to transcend, knowledge in the area, a vocation for service and empathy are required, with which the teaching body makes commitments and responds to the professional demands of its students and the institution in which it collaborates. It is concluded that transcendence becomes subjective, since its significance will depend not only on what those who are in front of the group think and do, but also on those who receive the teaching.